Deservingness in social policy. The concept, criteria and (un)deserving groups - Przybylska, Justyna (Zasługiwalność w kontekście polityki społecznej. Pojęcie, kryteria i (nie)zasługujące grupy, 2021)
The main purpose of this article is presentation of the concept of deservingness, which means dividing people into those who deserve to be supported and those who do not. In the paper, the deservingness models are analysed – the CARIN framework, the deservingness heuristic model and the RICE principles. The CARIN framework consists of five criteria – Control, Attitude, Reciprocity, Identity and Need, the RICE model of four criteria – Reciprocity, Identity, Control and Effort, and the deservingness heuristic model is based on the inherent ability to distinguish between ‘cheaters’ and ,’reciprocators’ in creating common good in society. The deservingness of particular groups and the influence of individual characteristics on its perception are also presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 127-137